2021
DOI: 10.1073/pnas.2105337118
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive staffing can mitigate essential worker disease and absenteeism in an emerging epidemic

Abstract: Essential worker absenteeism has been a pressing problem in the COVID-19 pandemic. Nearly 20% of US hospitals experienced staff shortages, exhausting replacement pools and at times requiring COVID-positive healthcare workers to remain at work. To our knowledge there are no data-informed models examining how different staffing strategies affect epidemic dynamics on a network in the context of rising worker absenteeism. Here we develop a susceptible–infected–quarantined-recovered adaptive network model using pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…These findings extend into the home nursing arena; previous studies have also shown that most families caring for children with tracheostomy were not satisfied with availability of nursing coverage [32] . Many patient and family respondents to our survey chose to opt-out of such care and “go it alone” without professional help to minimize risk of infection.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…These findings extend into the home nursing arena; previous studies have also shown that most families caring for children with tracheostomy were not satisfied with availability of nursing coverage [32] . Many patient and family respondents to our survey chose to opt-out of such care and “go it alone” without professional help to minimize risk of infection.…”
Section: Discussionmentioning
confidence: 51%
“…The average QOL scores for pediatric tracheostomy patients are lower than for patients with many other chronic illnesses [52] . QOL surveys of parents caring for children with tracheostomy find moderate distress and significant negative effects on mental health, [32] similar to caregivers of adults living with tracheostomy [30] .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…, corrobora com o artigo anterior quando afirma que os profissionais de saúde estão em maior risco de infecção pela COVID-19, fator que justifica a maior taxa de absenteísmo por saúde e custos assistenciais. Aguilar, et al (2021), Khorasanee, et al (2021), apontam o absenteísmo como um problema predominante na pandemia da COVID-19, esgotando as reposições de profissionais e por vezes, exigindo que os mesmos permanecessem trabalhando mesmo testando positivo para COVID-19, impactando na qualidade de vida do profissional e dos cuidados prestados. Concordando com o que foi dito anteriormente, Challener, et al (2021), utilizam como exemplo a gripe sazonal para apoio estratégico na atuação da pandemia pela COVID-19, avaliam o presenteísmo como uma fonte de redução de produtividade para os empregadores, especialmente na área da saúde.…”
Section: Discussionunclassified